2018
DOI: 10.1021/acs.iecr.8b00615
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Real-Time Optimization Scheme for Optimal Operation of Chemical Processes under Uncertainty: Proof of Concept in a Miniplant

Abstract: Real-time optimization (RTO) has gained growing attention during the past few years as a useful approach to boost process performance while safety and environmental constraints are satisfied. Despite the increasing acceptance of RTO in traditional industries such as petrochemical and refineries, its application to novel chemical processes remains limited. This can be partially explained by the fact that only inaccurate models are available and the performance of the traditional RTO scheme suffers in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The hydroformylation of 1-dodecene with synthesis gas is a reaction network, which was analyzed in detail in the DFG collaborative research center/Transregio 63 InPROMPT (see, e.g., refs ). In contrast to standard hydroformylation processes with short-chain alkenes, it is not possible to dissolve the long-chain alkene 1-dodecene in a polar solvent to get the nonpolar reactant and the polar catalyst system into contact because of the large polarity difference.…”
Section: Case Studymentioning
confidence: 99%
“…The hydroformylation of 1-dodecene with synthesis gas is a reaction network, which was analyzed in detail in the DFG collaborative research center/Transregio 63 InPROMPT (see, e.g., refs ). In contrast to standard hydroformylation processes with short-chain alkenes, it is not possible to dissolve the long-chain alkene 1-dodecene in a polar solvent to get the nonpolar reactant and the polar catalyst system into contact because of the large polarity difference.…”
Section: Case Studymentioning
confidence: 99%
“…While petrochemical and refining industries have accepted RTO in the past few years, its application to different chemical processes is still limited. To overcome this, Hernandez et al 22 proposed an RTO scheme applicable to a complex catalyzed process showing operational improvements despite modeling errors. A recent application on the bioethanol production showed that the use of closed-loop dynamic RTO in the ethanol distillation process can improve the profitability of this product as an environmentally friendly fuel 23 .…”
Section: Introductionmentioning
confidence: 99%
“…21 While petrochemical and refining industries have accepted RTO in the past few years, its application to different chemical processes is still limited. To overcome this, Hernandez et al 22 proposed an RTO scheme applicable to a complex catalyzed process showing operational improvements despite modeling errors.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, real-time optimization (RTO) appears as an adequate approach to adapt the operation to the current environment and aims. RTO makes use of a rigorous stationary model of the process to compute the operation conditions that optimize a predefined performance index, for example, minimization of the operating costs, maximization of product yields, or minimization of waste [8]. There are many examples in the literature of the benefits of using an RTO tool to facilitate the decision-making process [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…EC ev X ev,p ≤ EC ev,p ≤ EC ev X ev,p ∀ev ∈ E V, ∀p ∈ P (8) where EC ev and EC ev state the minimum and maximum evaporation load for a plant to operate correctly. With X ev,p we assure that EC ev,p take zero value for the products not linked to plant ev.…”
mentioning
confidence: 99%